A BIM-based model for constructability assessment of buildings design - Fadoul, Abdelaziz (2020)
Implementation of constructability principles in the construction industry has a potential return on investment concerning time and money. Existing empirical studies demonstrate that incorporating these principles into the initial stages of design maximises outcomes for all stakeholders, including designers, contractors, and clients. However, constructability encounters many challenges in practical implementation. One of the main obstacles is knowledge acquisition and representation, leading to the lack of a knowledge-based tool to model design constructability. Current methods demand laborious efforts and resources to execute assessment calculations and interpret their outcomes. The dynamic design process and the need for ongoing modifications in designed products necessitate revision of the constructability assessment routine, whenever design changes are introduced, and it is highly desirable that these revisions should be automated.